Differentiation and World Society. A Note on the Theory of Society by Niklas Luhmann - Thomas Kurtz (Journal of Sociological Research, 2024)
The topic of this essay is Niklas Luhmann‘s theory of society and, in particular, the relationship between differentiation and world society. Based on a reconstruction of the concept of differentiation in systems theory, the form of societal differentiation, and the distinction between primary and secondary forms of differentiation, this paper highlights a weakness of the theory and asks how its abstract level of analysis could be made more connectable to other theories of society. The suggestion is to focus more on the segmentary subdifferentiations of society-wide differentiated function systems in the world society.